PENGARUH MODEL PEMBELAJARAN COURSE REVIEW HORAY TERHADAP HASIL BELAJAR BIOLOGI SISWA PADA MATERI SISTEM PERTAHANAN TUBUH KELAS XI SMA - Ade Sitio, Dian Mars; Situmorang, Masni Veronika; Siagian, Gunaria (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
The purpose of this study is to determine: The effect of Course Review Horay Learning model on the learning outcomes of biology students in class XI material of the body's defense system at Senior hight school 1 Sidamanik in the academic year 2021/2022. This type of research is a quantitative research in which the research population includes all students of class XI SMA Negeri 1 Sidamanik in the academic year 2021/2022, so up to 175 students. The samples of this study were 70 students of classes XI IPA 2 and XI IPA 3. The instrument used in this study was a multiple choice test with a quasi-experimental research type and a non-equivalent control group design. The independent variable is Horay Course Overview and the dependent variable is learning outcomes. The results of the students' data were compared with the norms, and the study result data were analyzed using the N-Gain test and Independent Sample T-Test. The results showed that the